Respiratory Syncytial Virus-Infected Human Mesenchymal Stem Cells Overexpress Toll-like Receptors and Change the Pattern of Distribution of Their Cytoskeleton - César Alexis Rosales Velázquez; Laura Guadalupe Chavéz Gómez; Carlos Arturo Félix Espinosa; Mario Adan Moreno-Eutimio; Juan José Montesinos; Guadalupe R. Fajardo-Orduña; Rocio Tirado Mendoza (Viruses)
Acute respiratory tract infections (ARIs) are one of the major causes of morbimortality in children and adulthood. Furthermore, the respiratory syncytial virus (RSV) is the main pathogen in severe lower respiratory tract infections. In Mexico, RSV is the second cause of ARI, affecting mainly children and seniors. RSV infects the airway epithelium, including mesenchymal stem cells (MSCs). These cells express a variety of surface molecules which may function as viral receptors, i.e., Toll-like receptors (TLRs), but the consequences that viral infection has on their biological activities are poorly understood. The aim of this study is to determinate if RSV infection of MSC modifies the expression of stemness biomarkers, TLRs, and the organization of the cytoskeleton. To study the viral infection of MSCs, we determined the mRNA expression using qRT-PCR of SOX2, NANOG, and POU5F1; vimentin and actin; and TLRs 2, 4, and 6. In addition, we determined the cell surface expression of TLR 2 and 4 using flow cytometry. Our results showed that the infection did not change the mRNA expression of SOX2, NANOG, and POU5F1, but increased the mRNA expression of TLR4 and the cell surface expression. Meanwhile, the mRNA in the actin was unchanged, vimentin decreased, and the infection generated a redistribution of the cytoskeleton.